(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2018)
The General strength theory of reinforced concrete elements (GSTRCE) passed the long and many-sided examination and showed the considerable advantages: well concordance with experiments, essential economic effect, solving method unity for different strength problems. Simple practical methods for calculating according to GSTRCE and available for use by designers and students are developed. The algorithms of calculating of two practically important problems are stated: strength control and selection of needed longitudinal and lateral reinforcement. Problems solving are represented by using «manual» method and well-known and easy-to-use software complex MS Excel. The results of experimental verification of GSTRCE are stated and the ones show well convergence of theoretical strength to experimental one.